Feminist Epistemology and The Search For Liberating Knowledge - Rachmad Hidayat (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
This paper discusses problems in dealing with masculinized knowledge and scientific enterprises, and seeks alternative epistemological strategies in achieving liberating and un-dominated knowledge production. A general problem with